A valorização do patrimônio cultural de Val Veronês a partir da estratégia de desenvolvimento do turismo na Quarta Colônia, RS - Oliveira, Jocelito Oliveira de (2024)
The research’s central theme is the appreciation of the cultural heritage of the locality of Val Verones, which shares its political geography with the municipalities of Faxinal do Soturno – Rio Grande do Sul (RS) and Silveira Martins - RS. Based on the tourism development strategy, the research purpose is to focus on the social construction of this locality so that part of its heritage is highlighted based on current tourism development strategies in Quarta Colonia – RS. The research’s main objective is to analyze the community’s cultural heritage, its identity and distinctive elements for the appreciation of sustainable tourism. As specific: a) to present a theoretical contribution of the elements that constitute the cultural heritage and the relationship with the locality of Val Verones, as well as the touristic dimensions that encourage sustainable development; b) to verify which identity elements that constitute the cultural heritage of the locality of Val Verones and their specificities for inclusion in tourism development itineraries in the Quarta Colonia; and c) to create a digital Photobook of Val Verones, with records that identify the community's cultural heritage and endorse its memories and identities. The research is based on the proposal of the Postgraduate Program in Cultural Heritage at the Federal University of Santa Maria (UFSM), in the thematic area of architecture and material heritage. Methodologically, it is characterized as exploratory research, of a qualitative approach, in which data collection is primary and secondary for the conception of local identity with portraits and narratives of the experiences of the locality of Val Verones. As preliminary results, the identity of the cultural heritage of Val Verones is portrayed and presented in the content that is part of the final product, the digital Photobook.